Growth rates and ages of deep-sea corals impacted by the Deepwater Horizon oil spill. (July 2016) - Prouty, Nancy G.; Fisher, Charles R.; Demopoulos, Amanda W.J.; Druffel, Ellen R.M.
Abstract: The impact of the April 2010 Deepwater Horizon (DWH) spill on deep-sea coral communities in the Gulf of Mexico (GoM) is still under investigation, as is the potential for these communities to recover. Impacts from the spill include observation of corals covered with flocculent material, with bare skeleton, excessive mucous production, sloughing tissue, and subsequent colonization of damaged areas by hydrozoans. Information on growth rates and life spans of deep-sea corals is important for understanding the vulnerability of these ecosystems to both natural and anthropogenic perturbations, as well as the likely duration of any observed adverse impacts. We report radiocarbon ages and radial and linear growth rates based on octocorals ( Paramuricea spp. and Chrysogorgia sp.) collected in 2010 and 2011 from areas of the DWH impact. The oldest coral radiocarbon ages were measured on specimens collected 11 km to the SW of the oil spill from the Mississippi Canyon (MC) 344 site: 599 and 55 cal yr BP, suggesting continuous life spans of over 600 years for Paramuricea biscaya, the dominant coral species in the region. Calculated radial growth rates, between 0.34 μm yr −1 and 14.20 μm yr −1, are consistent with previously reported proteinaceous corals from the GoM. Anomalously low radiocarbon (Δ 14 C) values for soft tissue from some corals indicate that these corals were feeding on particulate organic carbon derived from an admixture of modern surface carbon and a low 14 C carbon source. Results from this work indicate fossil carbon could contribute 5–10% to the coral soft tissue Δ 14 C signal within the area of the spill impact. The influence of a low 14 C carbon source (e.g., petro-carbon) on the particulate organic carbon pool was observed at all sites within 30 km of the spill site, with the exception of MC118, which may have been outside of the dominant northeast–southwest zone of impact. The quantitatively assessed extreme longevity and slow growth rates documented here highlight the vulnerability of these long-lived deep sea coral species to disturbance.